EFFECTS OF ROLE-PLAY ON INDONESIAN JUNIOR HIGH SCHOOL STUDENTS’ SPEAKING SKILLS: A CLASSROOM ACTION RESEARCH STUDY - Yoniswan Yoniswan (STAIN Sultan Abdurrahman Kepulauan Riau, 2020)
The purpose of this study was to implement Role-Play method in improving English speaking abilities. This research is a classroom action research consisting of 2 cycles, each cycle consisting of planning, implementation, observation and reflection. The study was conducted in eight grade semester I of 2016/2017 academic year at SMP Negeri 17 Bintan with a total of 34 research subjects. The data collection methods used in this study are performance tests and observations. Quantitative method is used as data analysis. The results showed an increase in English speaking skills through Role Play method, in the first cycle with an average score of 63.06 percentage of completeness 17.65%, increased in the second cycle with an average score of 75.65 percentage of completeness 85.29%. It was concluded that Role Play method can improve English speaking skills.